Severe Chronic Upper Airway Disease (SCUAD) in children. Definition issues and requirements. Issue 7 (July 2015) - Karatzanis, A.; Kalogjera, L.; Scadding, G.; Velegrakis, S.; Kawauchi, H.; Cingi, C.; Prokopakis, E.
Abstract Objectives Upper airway diseases are extremely common, and a significant proportion of patients are not adequately controlled by contemporary treatment algorithms. The term SCUAD (Severe Chronic Upper Airway Disease) has been previously introduced to describe such cases. However, this term has not been adequately focused on children. Methods This study aims to address the necessity of the term, as well as further details specifically for children. For this purpose, a review was performed of the current literature, with specific focus on issues regarding SCUAD in children. Results Paediatric SCUAD represents a heterogeneous group of patients and has significant clinical and socioeconomic implications. Relevant literature is generally lacking and questions regarding definition and pathogenesis remain unanswered. Conclusions Accurate definition and acknowledgement of paediatric SCUAD cases may lead to better design of future clinical and molecular research protocols. This may provide improved understanding of the underlying disease processes, more accurate data regarding socioeconomic burden, and, above all, more successful treatment and prevention strategies.